Risk perception, accounting, and resilience in public sector organizations: A case study analysis - Mouhcine Tallaki; Enrico Bracci (Journal of Risk and Financial Management, 2021)
There are various factors that can affect an organization's ability to overcome a crisis and the uncertainties that arise thereafter. Little is known about the process of organizational resilience and the factors that can help or prevent it. In this paper, we analyzed how public sector organizations build resilience/traits of risks awareness, and in doing that, we derived some elements that could affect the process of resilience. In particular, drawing on the conceptual framework proposed by Mallak we analyzed an in-depth case study in a public sector organization (PSO) identifying some contextual dimensions implicated in the process of building resilience. In our analysis, we identified two main elements that affect resilience: Risk perception and the use of accounting. Results shown how risk perception is perceived as a trigger, while accounting is considered as an enforcer in the process of building resilience capacity. The results also show the way accounting is implicated in the management of austerity programs and supporting the creation of a resilient public sector organization. In our case, the risk has become an opportunity for change. In the face of these budget cuts, management began refocusing the company's mission from infrastructure maintenance to providing services with a market-based logic.
Keywords: 330; resilience capacity; cut-back management; crisis